Anionic and cationic Hofmeister effects are non-additive for guanidinium salts. Issue 15 (31st March 2017) - Balos, V.; Bonn, M.; Hunger, J.
Abstract : The interaction of spherical anions and cations with a model amide is additive, except for salts containing the guanidinium cation. Abstract : To understand specific ion effects on a molecular level we explore the effect of salts on the rotational mobility of a model amide using dielectric spectroscopy. Based on our previous studies on the effect of strong denaturing anions or cations, here we study the additivity of the anionic and cationic effect. Using salts consisting of denaturing spherical anions and spherical cations we find such salts to affect the amide according to what one expects based on the additive activity of the individual ions. The guanidinium (Gdm + ) cation appears to be a notable exception, as our results suggest that GdmI (and accordingly GdmSCN) is less efficient in hindering the rotation of the amide than KI or GdmCl.